1D layered velocity models and microseismic event locations: synthetic examples for a case with a single linear receiver array. (18th August 2017) - Akram, Jubran; Eaton, David W
Abstract: We discuss various aspects of 1D velocity-model building for application to microseismic data analysis. We generate simple synthetic example data using a widely used single linear array geometry. The synthetic data contain 30 sources with known locations for a reference model based on previous studies of the Barnett shale. We investigate several key factors that should be considered, including selection of the calibration technique, inclusion of a priori information such as lateral heterogeneity and parameter ranges, and choice of algorithm for travel time computations. For the source–receiver geometry considered here, hypocenter location errors (±6 m in X and ±12 m in Z ) can result from differently calibrated models only and without including the errors in picked arrival times and polarization estimates. We find that the errors in hypocenter locations are reduced (±3 m in X and ±6 m in Z ) when a model calibrated with multiple shots simultaneously is used. Using four different models (vertical fault, dipping layers, channels, and these effects combined), we demonstrate that systematic errors in hypocenter locations can result when a 1D layered model is used in lieu of a laterally heterogeneous subsurface. Finally, we show that event locations from a velocity model calibrated using direct-arrival times are more stable than from a model calibrated with first-arrival times.